Athenry Dominican Priory, north chancel wall, canopied tomb niche, base of jamb - O'Donovan, Danielle (My University, 2008)
Base of tomb niche jamb, moulding from top down comprises: necking roll, bell, scroll, plinth.
Canopied tomb
Keywords: scroll; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Dominican; Funerary monuments; Late Medieval; roll mouldings; plinth